PENGARUH AKUNTANSI PERTANGGUNGJAWABAN, KOMITMEN ORGANISASI, DAN PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL - Wiwik Pratiwi; Andari Asri Kartika (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
This study is meant to test empirically the influence of responsibility accounting, organizational commitment, and budget participation to the managerial performance on manufacturing companies in Jakarta. This research used survey method by questionnaries. The data were examined using descriptive statistics, test of validity and reliability, classic assumption test, multiple linear regression test, and hypothesis test by using SPSS versi 24.0 for windows. The results of this research showed that responsibility accounting, organizational commitment, and budget participation were effect on managerial performance partially and simultaneously. Keywords: responsibility accounting, organizational commitment, budget participation, managerial performance